2017
DOI: 10.25077/adj.v5i2.73
|View full text |Cite
|
Sign up to set email alerts
|

PERBEDAAN STABILITAS DIMENSI ANTARA CETAKAN ALGINAT YANG DIBERI DESINFEKTAN EKSTRAK DAUN ALPUKAT (Persea americana mill) DENGAN NATRIUM HIPOKLORIT

Abstract: Background  :  Alginat  is  one  of  the  most  used  impression  material  in  dentistry..  Alginate impression need to be disinfected to prevent cross-infection. One of effective natural material that can be used as disinfectant  is avocado  leaves.  The process  of disinfection  could interfered  the dimensional stability of alginate impression caused of imbibition properties in alginate itself. Purpose  : To determine  the differences  of dimensional  stability  of alginate  impression  which disinfected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…29 This study was also in accordance with the study of Amelia, et al which showed there was a change in dimensional stability which was still within the tolerance limits of alginate impression after 0.5% sodium hypochlorite was sprayed. 9 Disinfection of alginate impression with 10% castor oil in group C2 showed an effect on the dimensional stability of the study model. The results of this study were in accordance with previous study by Hasanah, et al concluded that disinfection of alginate impression by spraying 80% betel leaf solution resulted in insignificant changes in dimensional stability.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…29 This study was also in accordance with the study of Amelia, et al which showed there was a change in dimensional stability which was still within the tolerance limits of alginate impression after 0.5% sodium hypochlorite was sprayed. 9 Disinfection of alginate impression with 10% castor oil in group C2 showed an effect on the dimensional stability of the study model. The results of this study were in accordance with previous study by Hasanah, et al concluded that disinfection of alginate impression by spraying 80% betel leaf solution resulted in insignificant changes in dimensional stability.…”
Section: Discussionmentioning
confidence: 89%
“…The esterification reaction would produce esters and H2O, while alginate had properties that were easy to imbibe causing the increase of the disinfectant solution absorption and affecting the dimensional stability of the study model. 9,24,25 Group B1 showed the greatest decrease in the amount of C.albicans caused by the disinfectant effect of sodium hypochlorite where the chlorine content of the released sodium hypochlorite adheres to the cell cytoplasm which could destroy important C.albicans proteins. The results of this study were in accordance with the research of Bustos, et al in their research explaining that 0.5% so-dium hypochlorite could reduce the amount of bacteria including C.albicans in alginate impression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian yang dilakukan oleh nisa dkk menyatakan bahwa teknik penyemprotan lebih menguntungkan di lakukan, karena teknik ini dapat mengurangi terpaparnya cetakan alginat terhadap larutan desinfektan, alasan tersebut merupakan mengapa tidak terhjadi perubahan stabilitas dimensi alginat setelah dilakukan desinfeksi dengan larutan daun sirih 80%. [26], [29], [30] Sinnun Maxillofacial Journal. Vol.…”
Section: Pembahasanunclassified
“…Alginat memiliki sifat yang mudah mengalami imbibisi sehingga bila ekstrak daun teh hijau yang mengandung senyawa fenol berkontak dengan alginat dapat menyebabkan ekspansi hasil cetakan. 15 Pada penelitian ini dilakukan pengukuran dimensi anteroposterior dan mediolateral untuk memastikan akurasi stabilitas dimensi alginat setelah dilakukan desinfeksi agar tidak memengaruhi rencana perawatan selanjutnya. 16…”
Section: Bahasanunclassified